FRI0579 PREDNISONE VERSUS STANDARD THERAPY IN SYDENHAM'S CHOREA: RESULTS FROM A RETROSPECTIVE STUDY. (June 2019) - Favaretto, Elena; Gortani, Giulia; Simonini, Gabriele; Pastore, Serena; Cimaz, Rolando; Tommasini, Alberto; Taddio, Andrea
Abstract : Background: Sydenham's chorea is a major and delayed manifestation of acute rheumatic fever [1] and is considered to be a prototype of an autoimmune disorder triggered by an infectious agent. Aside from conventional symptomatic treatment (carbamazepine, valproate, neuroleptics), the use of steroids has also been advocated, mainly in severe, drug-resistant cases or if clinically disabling side effects develop with first line therapies. However the evidence of corticosteroids efficacy is weak. Objectives: To describe the efficacy of corticosteroids therapy versus standard therapy in children affected by Sydenham's Chorea in a cohort of Italian patients with acute rheumatic fever (ARF). Methods: A retrospective observational study was conducted. The hospital records for all children diagnosed as having ARF between January 2007 and December 2017 in the Pediatric Rheumatology Division of the Meyer Children Hospital (Florence) and IRCCS Burlo Garofolo (Trieste) were reviewed. The diagnosis of ARF was made by pediatric rheumatologists and all the children discharged with a ICD 9 code consistent with ARF were included. For the purpose of the study only patients with Sydenham's Chorea were enrolled. Files were analyzed for demographic data, clinical and laboratory findings on admission and during the hospital stay and patients with incomplete information were excluded. Time and resolution of choreic symptoms were evaluated in consideration of presence or absence of corticosteroid therapy. Results: Thirty patients were enrolled; 23 out of 30 (76%) had generalized chorea. 15 (50%) were treated with prednisone (2 mg/kg/day in a single administration per day for 14 days before tapering), 11 (36.6%) were not treated with medications and 4 (13.3%) received pimozide or sodium valproate. We considered together patients who did not receive any specific therapy for chorea and patients who received only symptomatic anti-chorea drugs (pimozide in 3 cases and sodium valproate in 1 case). Therefore we obtained two groups of 15 participants each: "Prednisone group" and "Standard therapy group". The time required for clinical improvement in the two groups appeared statistically different (P = 0.002). In "Prednisone group" the median time for improvement was 4.0 days (interquartile range: 3) whereas in "Standard therapy group" it was 16.0 days (interquartile range: 16). Furthermore, the "Prednisone group" had a median remission time of 30.0 days (interquartile range: 34) whereas "Standard therapy group" presented a median remission time of 135.0 days (interquartile range: 309) (P < 0.001). At least one episode of relapse occurred in 1 (6.7%) out of 15 patients in the "Prednisone group" and in 3 patients (20%) in the "Standard therapy group". However, the difference is not statistically significant (p = 0.598). Conclusion: Our study shows that corticosteroid therapy is associated with a faster resolution of Sydenham's Chorea's symptoms compared to treatments considered of first line, such as: no therapy, valproate or pimozide. Disclosure of Interests: Elena Favaretto: None declared, Giulia Gortani: None declared, Gabriele Simonini Grant/research support from: Abbvie, Speakers bureau: Abbvie, Serena Pastore: None declared, Rolando Cimaz: None declared, Alberto Tommasini: None declared, Andrea Taddio: None declared